1998
DOI: 10.1105/tpc.10.10.1699
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant of Arabidopsis Lacking a Chloroplastic Isoamylase Accumulates Both Starch and Phytoglycogen

Abstract: In this study, our goal was to evaluate the role of starch debranching enzymes in the determination of the structure of amylopectin. We screened mutant populations of Arabidopsis for plants with alterations in the structure of leaf starch by using iodine staining. The leaves of two mutant lines stained reddish brown, whereas wild-type leaves stained brownish black, indicating that a more highly branched polyglucan than amylopectin was present. The mutants were allelic, and the mutation mapped to position 18.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(84 citation statements)
references
References 34 publications
1
83
0
Order By: Relevance
“…Recent structural studies with ISA1 from the green alga Chlamydomonas reinhardtii indicate that the enzyme has a relatively low affinity towards tightly spaced branches, supporting its proposed role in glucan trimming model [335]. Nevertheless, although ISA mutants accumulate large quantities of phytoglycogen (in maize, this is the basis of some "sweetcorn" varieties), many of these mutants are able to synthesize some starch [320,336], indicating that ISA activity is not a mandatory requirement for crystalline-competent amylopectin formation. Other studies suggest that glucan chain composition is important in the process of granule formation, for example, some japonica rice lines (with reduced SSIIa, see above) with isa1 mutation completely lack starch [337].…”
Section: Debranching Enzymesmentioning
confidence: 99%
“…Recent structural studies with ISA1 from the green alga Chlamydomonas reinhardtii indicate that the enzyme has a relatively low affinity towards tightly spaced branches, supporting its proposed role in glucan trimming model [335]. Nevertheless, although ISA mutants accumulate large quantities of phytoglycogen (in maize, this is the basis of some "sweetcorn" varieties), many of these mutants are able to synthesize some starch [320,336], indicating that ISA activity is not a mandatory requirement for crystalline-competent amylopectin formation. Other studies suggest that glucan chain composition is important in the process of granule formation, for example, some japonica rice lines (with reduced SSIIa, see above) with isa1 mutation completely lack starch [337].…”
Section: Debranching Enzymesmentioning
confidence: 99%
“…Sta7 mutants have no isoamylase activity and starch is replaced by a small amount of phytoglycogen . More recently, dbe1 mutants of Arabidopsis devoid of plastidic isoamylase were isolated and shown to accumulate phytoglycogen and small amounts of starch in the leaf (Zeeman et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a discontinuous synthetic cycle for amylopectin formation in which isoamylase is essential in order to remove a-1,6-branches that do not ®t into the semicrystalline structure of amylopectin. This model was questioned on the basis of an Arabidopsis mutant line that lacks chloroplastic isoamylase and accumulates both starch and phytoglycogen within the same cell (Zeeman et al 1998). This study suggested that isoamylase is not essential in the formation of amylopectin but acts, along with other amylolytic enzymes, on soluble polyglucans in order to prevent phytoglycogen accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequence studies in a wide range of plants show that there are four debranching enzyme genes in the plant genome, three isoamylase-like genes (isoamylases 1, 2 and 3) and one pullulanase-(or limit dextrinase-)type gene (Morell & Myers 2005). Mutation studies in a range of species, including rice (Nakamura et al 1996), maize (James et al 1995), barley (Burton et al 2002), Arabidopsis (Zeeman et al 1998) and Chlamydomonas (Mouille et al 1996), demonstrate that mutation in isoamylase 1 leads to a low-starch high-phytoglycogen phenotype. More recent data suggest that an identical phenotype is recovered when isoamylase 2 is mutated and it is suggested that this is because isoamylase 1 and 2 form a complex whose function is abolished if either is absent.…”
Section: Starch Biosynthesis and Functionalitymentioning
confidence: 99%